Blockade of TMPRSS2-mediated priming of SARS-CoV-2 by lactoferricin - Ohradanova-Repic, Anna; Skrabana, Rostislav; Gebetsberger, Laura; Tajti, Gabor; Baráth, Peter; Ondrovičová, Gabriela; Praženicová, Romana; Jantova, Nikola; Hrasnova, Patricia; Stockinger, Hannes; Leksa, Vladimir (Frontiers in Immunology, 2022)
In addition to vaccines, there is an urgent need for supplemental antiviral therapeutics to dampen the persistent COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The transmembrane protease serine 2 (TMPRSS2), that is responsible for proteolytic priming of the SARS-CoV-2 spike protein, appears as a rational therapeutic target. Accordingly, selective inhibitors of TMPRSS2 represent potential tools for prevention and treatment of COVID-19. Previously, we identified the human milk glycoprotein lactoferrin as a natural inhibitor of plasminogen conversion to plasmin, a serine protease homologous to TMPRSS2. Here, we tested whether lactoferrin and lactoferricin, a biologically active natural peptide produced by pepsin-mediated digestion of lactoferrin, together with synthetic peptides derived from lactoferrin, were able to block TMPRSS2 and SARS-CoV-2 infection. Particularly, we revealed that both lactoferricin and the N-terminal synthetic peptide pLF1 significantly inhibited: i) proteolytic activity of TMPRSS2 and plasmin, ii) proteolytic processing of the SARS-CoV-2 spike protein, and iii) SARS-CoV-2 infection of SARS-CoV-2-permissive cells. Thus, natural and synthetic peptides derived from lactoferrin represent feasible candidates for supporting prevention and treatment of COVID-19.